The Giant of Tripoli: The Case of Late Recognition and Management of an Extreme Acromegalic Gigantism in Resource-Poor Settings - Beshyah, Salem A. (Journal of Diabetes and Endocrine Practice, 2022)
Background There are a few studies from the Middle East and North Africa. Several notable cases of acromegaly and giantism in the west found their way to public life and media.Case History One of the cases is discussed in this article. The case lived between 1943 and 1991. He was one of few individuals in medical history to reach or surpass 8 feet in height. In the 1960s, he reportedly underwent repeated (perhaps 4) pituitary surgery at 17 in Rome, Italy, to halt his growth. A few photos and one short video clip in Italian demonstrate his physical features. He was one of the tallest basketball players ever at 245 cm, though when he featured as a basketball player, he was closer to 239 cm and played for Libya. He was a medical anomaly and the eighteenth tallest person in the history of the world. He was also credited with being the tallest actor in history by appearing in a single Italian fantasy drama movie in 1969. He died in 1991 due to heart disease.Conclusion The case presented in this vignette is depicted in the public domain and is imprinted in the folk memory of the residents of Tripoli, Libya. However, due to its uniqueness, it deserves a place in the regional medical literature.
Keywords: history of medicine; acromegaly; gigantism; Tripoli; Libya; Middle East; North Africa